Association between antiretroviral therapy adherence and employment status: systematic review and meta-analysis - Jean B Nachega; Olalekan A Uthman; Karl Peltzer; Lindsey A Richardson; Edward J Mills; Kofi Amekudzi; Alice Ouédraogo (The World Health Organization, 2015)
Objective To assess the association between the employment status of human immunodeficiency virus (HIV)-infected individuals and adherence to antiretroviral therapy (ART). Methods We searched the Medline, Embase and Cochrane Central Register of Controlled Trials databases for studies reporting ART adherence and employment status published between January 1980 and September 2014. Information from a wide range of other sources, including the grey literature, was also analysed. Two independent reviewers extracted data on treatment adherence and study characteristics. Study data on the association between being employed and adhering to ART were pooled using a random-effects model. Between-study heterogeneity and sources of bias were evaluated. Findings The meta-analysis included 28 studies published between 1996 and 2014 that together involved 8743 HIV-infected individuals from 14 countries. The overall pooled odds ratio (OR) for the association between being employed and adhering to ART was 1.27 (95% confidence interval, CI: 1.04-1.55). The association was significant for studies from low-income countries (OR: 1.85, 95% CI: 1.58-2.18) and high-income countries (OR: 1.33, 95% CI: 1.02-1.74) but not middle-income countries (OR: 0.94, 95% CI: 0.62-1.42). In addition, studies published after 2011 and larger studies showed less association between employment and adherence than earlier and small studies, respectively. Conclusion Employed HIV-infected individuals, particularly those in low- and high-income countries, were more likely to adhere to ART than unemployed individuals. Further research is needed on the mechanisms by which employment and ART adherence affect each other and on whether employment-creation interventions can positively influence ART adherence, HIV disease progression and quality of life.